Last updated at May 29, 2018 by Teachoo

Transcript

Ex 4.1,14 Prove the following by using the principle of mathematical induction for all n ∈ N: ("1 + " 1/1) ("1+" 1/2) ("1+" 1/3)….. ("1+ " 1/𝑛) = (n + 1) Let P(n) : ("1 + " 1/1) ("1+" 1/2) ("1+" 1/3)….. ("1+ " 1/𝑛) = (n + 1) For n = 1, L.H.S = ("1 + " 1/1) = 1 + 1 = 2 R.H.S = (1 + 1) = 2 Thus, L.H.S. = R.H.S , ∴P(n) is true for n = 1 Assuming P(k) is true P(k) : ("1 + " 1/1) ("1+" 1/2) ("1+" 1/3)….. ("1+ " 1/𝑘) = (k + 1) We will prove P(k + 1) is true R.H.S = ((k + 1) + 1) L.H.S = ("1 + " 1/1) ("1+" 1/2) ("1+" 1/3)….. ("1+ " 1/((k +1) )) ∴ By the principle of mathematical induction, P(n) is true for n, where n is a natural number

Ex 4.1

Ex 4.1, 1
Important

Ex 4.1, 2

Ex 4.1, 3 Important

Ex 4.1, 4

Ex 4.1, 5 Important

Ex 4.1, 6

Ex 4.1, 7 Important

Ex 4.1, 8 Important

Ex 4.1, 9

Ex 4.1, 10

Ex 4.1, 11 Important

Ex 4.1, 12

Ex 4.1, 13 Important

Ex 4.1, 14 You are here

Ex 4.1, 15 Important

Ex 4.1, 16 Important

Ex 4.1, 17 Important

Ex 4.1, 18 Important

Ex 4.1, 19

Ex 4.1, 20

Ex 4.1, 21 Important

Ex 4.1, 22

Ex 4.1, 23 Important

Ex 4.1, 24 Important

About the Author

Davneet Singh

Davneet Singh is a graduate from Indian Institute of Technology, Kanpur. He has been teaching from the past 10 years. He provides courses for Maths and Science at Teachoo.